(untitled) (Eurasian Journal of Religious Studies, 2021)
The religious, political and social reasons for the emergence of the Shi’ite sect in the historical arena, which led to the first major divisions in the history of Islam are analyzed in the article. Based on historical data, researchers disagree on the views of the Prophet’s cousin, deputy and son-in-law (peace and blessings be upon him), as well as the inability of Ali, the leader of Ahl al-Bayt, to be the first caliph. It also reflects Ali’s personal qualities that influenced his inauguration. There is scientific evidence that the faith group supporting his caliphate became a movement, was persecuted by rivals, divided into several branches, supported by some rulers at different times in history, and formed states such as Buwayh, Fatimid, Safavid, Akkoy and Karakoy. It examines the significance or insignificance of the historical events that led to the Shiite sects rejecting the early caliphs as unjust. It also explains the reasons for the spread of Shiism in Yemen and Bahrain outside the Hejaz. Also scientifically analyzed the factors that influenced the emergence of the concepts of "Mahdi", "invisible imam", "crown", "reincarnation", "Veda" among Shiites. The object of the scientific article is also the different views of the Sufi communities of the eastern direction on the prophets Kyzyr and Elijah, whose names are mentioned in the Koran. Key words: Shiism, Khalifa, Ahl al-Bayt, Mahdi, Imam.